Degree of Handedness, but not Direction, is a Systematic Predictor of Cognitive Performance - Prichard, Eric; Propper, Ruth E.; Christman, Stephen D. (Frontiers in Psychology, 2013)
A growing body of evidence is reviewed showing that degree of handedness (consistent versus inconsistent) is a more powerful and appropriate way to classify handedness than the traditional one based on direction (right versus left). Experimental studies from the domains of episodic memory retrieval, belief updating/cognitive flexibility, risk perception, and more are described. These results suggest that inconsistent handedness is associated with increased interhemispheric interaction and increased access to processes localized to the right cerebral hemisphere.